Peningkatan Produktivitas Perkebunan di Lahan Kebun Melon dan Semangka melalui Pemanfaatan Traktor mini/Cultivator mini di Kelurahan Lalolang Kecamatan Tanete Rilau Kabupaten Barru - Ishak Ismail, Andi Muhammad; Zulhayyir, Zulhayyir; Syamsiah, Syamsiah (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program aims to increase the productivity of melon and watermelon plantations in Lalolang Village, Tanete Rilau District, Barru Regency, through the use of mini tractors or mini cultivators. The project partners are farmer groups that have relied on manual tillage using hoes and animal power, resulting in suboptimal time efficiency and yields. The intervention involved introducing mini tractors as a modern, fuel-efficient and easy-to-operate agricultural mechanization tool. Activities included outreach on the benefits of the equipment, training on its use and maintenance, and hands-on practice on partner farms. Initial results indicate an increase in tillage efficiency of up to 60% and a 40% reduction in labor costs. Furthermore, farmers gained experience with new technologies, contributing to increased crop productivity and income. This program also has implications for increasing farmer groups' independence in land management and accelerating the adoption of sustainable agricultural technologies at the local level.